Effect of temperature on the process of pressing organic raw materials - Rindyuk, Dmitry; Ryabokon, Natalia (My University, 2014)
The process of extrusion pelletizing particulate materials, such as sunflower and buckwheat husk, oak and pine chips, wheat straw and bran has been considered. It was investigated the effect of temperature of raw materials, compacting pressure and the diameter of the press-matrix on quality of fuel pellets.
Keywords: температура; temperature; частицы; частинки; particles; матеріали; материалы; materials; біопаливо; биотопливо; biofuels; гранулювання; гранулирования; pelleting; кафедра теоретичної механіки та ресурсоощадних технологій